Mhealth in Tuberculosis Treatment: A new approach to improve adherence - Rajavardhana, T.; Rajanandh, M.G.; Geethavani, M.; Sreedhar, V. (International Journal of Psychosocial Rehabilitation, 2020)
Adherence to tuberculosis (TB) treatment is very important in promoting individual and public health. As Poor adherence may result in suffering, disease worsening and death as well as it again leads to increased economic burden to the patients as length of the treatment regimen increases and drug resistance develops.1 Exploring newer ways in improving adherence is very essential with growing non adherence. Mobile health (mHealth) holds considerable promise to improve quality and efficiency in health care.2 Yet its potential in Tuberculosis remains largely unexplored 3, 4. and there is a lack of patient-centered mHealth approaches in response to the complexity of real life.5 Also lacking are ethical evaluations of mHealth interventions6,7. The planning, implementation, and evaluation of mHealth interventions for Tuberculosis treatment adherence must be guided by values as much as by technical innovation.